2005
DOI: 10.2166/wst.2005.0548
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic parameters estimation in an anaerobic digestion process using successive quadratic programming

Abstract: In this work, an optimization method is implemented in an anaerobic digestion model to estimate its kinetic parameters and yield coefficients. This method combines the use of advanced state estimation schemes and powerful nonlinear programming techniques to yield fast and accurate estimates of the aforementioned parameters. In this method, we first implement an asymptotic observer to provide estimates of the non-measured variables (such as biomass concentration) and good guesses for the initial conditions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Hiderani et al [37], who used anaerobic respirometry to determine digestion kinetics. Additional data are given in [12,16,[38][39][40][41][42][43][44][45].…”
Section: Simple Models and Principal Kineticsmentioning
confidence: 99%
“…Hiderani et al [37], who used anaerobic respirometry to determine digestion kinetics. Additional data are given in [12,16,[38][39][40][41][42][43][44][45].…”
Section: Simple Models and Principal Kineticsmentioning
confidence: 99%
“…In many publications about non linear observers for the design of FDI systems, the residuals are based in the error of the estimation obtained by the observer [ 9 ]. In biological processes, due to their non linear nature, in the majority of cases they are not completely observable, therefore it is more appropriate to consider some relationships among parameters, instead of attempting to estimate them individually [ 10 , 11 ]. The work presented in [ 11 ] explores a methodology to determine the global state and parameters of biological reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Criteria on the alkalinity references are rigorously adapted as a function of the true state variables and then expressed directly as control objectives upon these variables 9. In order to deal with important uncertainties on kinetic parameters and process inputs, the proposed control law is based upon adaptive approaches 10–12 combined with robust interval observer schemes to estimate guaranteed interval of unmeasured variables 13 that are further used in the calculation of the control efforts. It is shown that the proposed MIMO controller was able to guarantee the operational stability of the AD process under the influence of parameter uncertainty and load disturbances.…”
Section: Introductionmentioning
confidence: 99%